Pengaruh Profitabilitas, Ukuran Perusahaan, dan Komisaris Independen Terhadap Agresivitas Pajak - Melanie Octavia; Adila Sari; Pricillia D. Valentine; Rizky Raditya Pratama; An Suci Azzahra (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study analyses the effect of profitability, company size, and the number of independent commissioners on tax aggressiveness in the health sector listed on the Indonesia Stock Exchange during the period 2021-2024. Tax aggressiveness refers to the company's efforts to reduce tax liabilities in order to increase their economic value. The method applied in this study is a quantitative approach, with a population consisting of 18 companies in the health sector listed on the IDX, from which a sample of 15 companies was taken through purposive sampling. The data used was 40, after eliminating data that were considered outliers. Analyses were conducted by checking classical assumptions as well as conducting tests individually and jointly. The findings showed that individually, the three variables did not show a significant influence on tax aggressiveness. Overall, they also did not contribute significantly with a significance value of 0.292. This suggests that there are other more dominant factors that influence aggressive tax policies in these companies.